Confucian Moral Education in the Ta Shueh and Analects - Ibana, Ranier A (Archīum Ateneo, 2020)
Confucian philosophy has always considered education as a mechanism to improve the quality of life in society. The Confucian classic, Ta Hsueh and the Analects emphasize this pivotal role of education. The ethics of education and life in the family also has a deep impact on government and business enterprises. Each one plays assigned roles and lives by the rules that govern his or her station in social life. The ninth chapter of the Ta Shueh teaches that "correct deportment" can rectify a whole country. Projecting the ethics of the family to the social order and extending the ethos of particular cultural practices to the global community, however, poses certain problems. The scope of the latter is much more extensive than the family and broader than the cultural practices of particular nation-states. When family relations are preferred over that of others, authoritarian political power will not be too far behind. This paper is an investigation of the nature and limits of Confucian educational philosophy and its influence on society against the backdrop of globalization.